Poria cocos polysaccharide prevents alcohol-induced hepatic injury and inflammation by repressing oxidative stress and gut leakiness - Jiang, Yue-hang; Wang, Lei; Chen, Wei-dong; Duan, Yu-ting; Sun, Ming-jie; Huang, Jia-jing; Peng, Dai-yin; Yu, Nian-jun; Wang, Yan-yan; Zhang, Yue (Frontiers in Nutrition, 2022)
Alcoholic liver disease (ALD), a major chronic liver disease worldwide, is accompanied by hepatic inflammation, gut leakiness, and abnormal oxidative stress. Active Poria cocos polysaccharide (PCP-1C) was screened based on hepatoprotective activity in our previous study. Here, we investigated whether PCP-1C protects against binge alcohol-induced hepatic inflammation, gut leakiness, and abnormal oxidative stress. PCP-1C significantly improved the alcohol-induced liver injury, characterized by decreased serum biochemical parameters, alleviated hepatic steatosis, and reduced lipid accumulation caused by ALD. Besides, PCP1C treatment not only reduced hepatic inflammation by inhibiting the TLR4/NF-κB signaling pathway but also improved hepatocyte apoptosis by inhibiting the CYP2E1/ROS/MAPKs signaling pathway. Our study showed that PCP-1C could also repair the intestinal barrier and reduce lipopolysaccharide (LPS) leakage. Generally, PCP-1C shows a good therapeutic effect on ALD, which may play a protective role by reducing the release of inflammatory factors, inhibiting oxidative stress and apoptosis, and improving intestinal barrier injury.